2015
DOI: 10.1002/nag.2382
|View full text |Cite
|
Sign up to set email alerts
|

On the understanding of cyclic interaction mechanisms in an energy pile group

Abstract: SummaryIntegrating ground heat exchanger elements into concrete piles is now considered as an efficient energy solution for heating/cooling of buildings. In addition to the static load of buildings, the concrete piles also undergo a cycle of thermal deformation. In the case of single energy pile, calculation methods already exist and permit to perform a proper geotechnical design. In the case of energy pile group, the thermo‐mechanical interactions within the group are more complex. Very few experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The results show that heating loads cause additional stress and displacement in thermoactive piles, and increase the mobilization and end-bearing capacity to a large extent. Suryatriyastuti et al (2016) used a nonlinear cyclic plasticity model to show that the long-term pile capacity would decrease with cycles due to repetitive stress reversals.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that heating loads cause additional stress and displacement in thermoactive piles, and increase the mobilization and end-bearing capacity to a large extent. Suryatriyastuti et al (2016) used a nonlinear cyclic plasticity model to show that the long-term pile capacity would decrease with cycles due to repetitive stress reversals.…”
Section: Introductionmentioning
confidence: 99%
“…Several constitutive relationships used in FE analyses of soils do not consider thermo-mechanical behaviour but account for different ways to incorporate soil nonlinearity during mechanical loading. Specifically, Suryatriyastuti et al 2016 2015used an interface friction angle smaller than that of the soil and a refined mesh near the interface, while Suryatriyastuti et al (2016) used a bounding surface plasticity formulation for the interface. Gawecka et al (2016, 2017) used a full-coupled thermo-hydro-mechanical FE model to model the impact of transient heat transfer and water flow on soil-structure interaction in energy piles and found that thermally-induced stresses in energy piles dissipate with time as the surrounding subsurface reacts to the changes in pile temperature.…”
Section: Pilesmentioning
confidence: 99%
“…Gawecka et al (2016, 2017) used a full-coupled thermo-hydro-mechanical FE model to model the impact of transient heat transfer and water flow on soil-structure interaction in energy piles and found that thermally-induced stresses in energy piles dissipate with time as the surrounding subsurface reacts to the changes in pile temperature. Cyclic effects have been considered in several finite element analyses, with plastic deformations obtained through the constitutive model of the soil (Ng et al 2015) or through the soilpile interface constitutive model (Suryatriyastuti et al 2016). Many of the models mentioned above were validated using field data from Laloui et al (2006) or Bourne-Webb et al (2009), although Rotta Loria et al (2015a, 2015b found that FE analyses could also be validated using centrifuge modelling results.…”
Section: Pilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in situ tests (McCartney & Murphy, 2012;Murphy et al, 2014;Mimouni & Laloui, 2015) and numerical analyses (Di Donna & Laloui, 2014;Jeong et al, 2014;Salciarini et al, 2015;Di Donna et al, 2016;Suryatriyastuti et al, 2016) have recently investigated this problem for energy pile groups. To date, however, knowledge of the development and impact of thermally induced group effects among closely spaced energy piles on their thermo-mechanical behaviour has been limited due to the lack of field data about the exploitation of energy piles that either partially or entirely operate as geothermal heat exchangers for timescales that are typical of practical applications.…”
Section: Introductionmentioning
confidence: 99%